2020
DOI: 10.1016/s0140-6736(20)30806-0
|View full text |Cite
|
Sign up to set email alerts
|

Urgent dental care for patients during the COVID-19 pandemic

Abstract: admission for the management of acute dental infections that threaten the airway and require intensive care.Patients with substantial swellings can progress to life-threatening emergencies, which can increase risks in the setting of reduced health-care availability. For such patients, extractions of the causative pathogenic teeth should be prioritised over resto rative rescue, and input from dedicated oral surgery and oral and maxillofacial services and close follow-up should be instigated as locally appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 1 publication
1
127
0
20
Order By: Relevance
“…In case of urgent not-deferable surgical procedures, all subjects received a surgical treatment as atraumatic as possible [14]. All therapies were carried out under antibiotic therapy according to the pathological condition and after disinfection of the oral cavity with chlorhexidine 0.20%.…”
Section: U Groupmentioning
confidence: 99%
“…In case of urgent not-deferable surgical procedures, all subjects received a surgical treatment as atraumatic as possible [14]. All therapies were carried out under antibiotic therapy according to the pathological condition and after disinfection of the oral cavity with chlorhexidine 0.20%.…”
Section: U Groupmentioning
confidence: 99%
“…The potential for transmission via salivary bioaerosols poses a particularly significant danger to healthcare workers that operate in close proximity to the face and oral cavities, such as dental practitioners; oral-maxillofacial surgeons; ear, nose, and throat (ENT; otorhinolaryngology) surgeons; and ophthalmologists, especially when carrying out procedures that generate aerosols [41,42]. Indeed, the COVID-19 outbreak has resulted in the significant curtailment of services provided by these health professionals, posing a significant public health problem, as important and highly prevalent oral and ENT conditions cannot be adequately treated during this epidemic [41][42][43][44]. Thus, understanding the role of salivary aerosols in COVID-19 transmission is imperative, as is an appreciation of the effect of various environmental and therapeutic interventions on the extent of aerosol creation, and the development of strategies to minimise the risk to both health professionals and patients alike.…”
Section: Salivary Droplets and Bioaerosols: A Hidden Foe In Covid-19mentioning
confidence: 99%
“…However, healthcare professionals will not be staying home. Indeed, they belong to a group of individuals who will be particularly vulnerable to contracting the infection (Dave et al 2020), which has been reported to be as high as 29% in Wuhan, China (Wang et al 2020). In this context, the Occupational Safety and Health Administration (OSHA) within the Department of Labor, USA, has developed an occupational risk pyramid which defines the risk of healthcare providers based on exposure (https:// www.osha.gov/Publications/OSHA3990.pdf; United States, Department of Labour).…”
Section: Introductionmentioning
confidence: 99%